The morphology and the distribution of gut endocrine cells in the gastrointestinal tract of Indonesian native chicken were studied using Grimelius staining method. The endocrine cells were polymorph, round oval, triangular or pyramidal in shapes and scattered among the cells in the mucosal epitheli-um and glands of all portions of the gastrointestinal tract from stomach to rectum. These cells were characterized by the presence of basally located cytoplasmic granules that react positively with th - Aryani Sismin Sastyaningtijas; Savitri Novelina; Srihadi Agungpriyono (Media Veteriner, 1999)
The morphology and the distribution of gut endocrine cells in the gastrointestinal tract of Indonesian native chicken were studied using Grimelius staining method. The endocrine cells were polymorph, round oval, triangular or pyramidal in shapes and scattered among the cells in the mucosal epitheli-um and glands of all portions of the gastrointestinal tract from stomach to rectum. These cells were characterized by the presence of basally located cytoplasmic granules that react positively with the silver granules of the staining method. Two types of endocrine cells were observed in this stu-dy included open type and closed type. In the open type cells cytoplasmic elongation reached the intestinal or glandular lumen. Closed type cells possessed no such elongation but there was cytoplasmic processes run in the basal membrane. Open cells were largely distributed in the intestine while closed type cells with basally cytoplasmic processes were numerous in the gizzard. In general the endocrine cells were numerous in the jejunum of the small intestine. In the distal portion of large intestine we found clusters of endo-crine cells in the glands. The morphology and distribution pattern observed was discussed in relation with their possible functional implications.